Revitalisasi Perpustakaan untuk Meningkatkan Literasi Siswa SD Negeri 2 Babussalam - Rizky Pratama, Andika; Hana Febriana, Baiq; Mutmainnah; Lusiana, Putri (Rengganis Jurnal Pengabdian Masyarakat, 2024)
Libraries that do not function optimally result in very low student literacy interest and concentration so that revitalizing the library is mandatory to increase student literacy interest. The method carried out is by diffusion of science and technology, namely rebuilding the library by rearranging reading books, changing the atmosphere of the library. The library can regain its role as a source of information for students, based on student visits to the library to increase so that student literacy increases. The involvement of various parties plays an important role in the implementation of revitalization and there needs to be continuous action taken to continue to maintain the condition and function of the library. The result of the service is the improvement of literacy of SD Negeri 2 Babussalam students and the ability to manage libraries by the school